Demography of endangered juvenile green turtles in face of environmental changes: 10 years of capture-mark-recapture efforts in Martinique - Pierre Lelong; Aurélien Besnard; Marc Girondot; Caroline Habold; Fabienne Priam; Mathieu Giraudeau; Guillaume Le Loc'h; Aurélie Le Loc'h; Pascal Fournier; Christine Fournier-Chambrillon; Paco Bustamante; Sophie M. Dupont; et al. (Biological Conservation, 2024)

Vegetation changes in the Grote Nete valley (Campine region, Belgium) during the Boreal: a response to the 9.3 ka event? - Frederike Verbruggen; Wim Z. Hoek; Jeroen Verhegge; Ignace Bourgeois; Mathieu Boudin; Lucy M. Kubiak-Martens; Caroline Ryssaert; Philippe Crombé (Vegetation History and Archaeobotany, 2023)

Broad‐front migration leads to strong migratory connectivity in the lesser kestrel ( Falco naumanni ) - Maurizio Sarà; Salvatore Bondì; Ana Bermejo; Mathieu Bourgeois; Mathias Bouzin; Javier Bustamante; Javier de la Puente; Angelos Evangelidis; Annagrazia Frassanito; Egidio Fulco; Giuseppe Giglio; Gradimir Gradev; et al. (Journal of Biogeography, 2019)
Aim Migratory animals regularly move between often distant breeding and non‐breeding ranges. Knowledge about how these ranges are linked by movements of individuals from different populations is crucial for unravelling temporal variability in population spatial structuring and for identifying environmental drivers of population dynamics acting at different spatio‐temporal scales. We performed a large‐scale individual‐based migration tracking study of an Afro‐Palaearctic migratory raptor, to determine the patterns of migratory connectivity of European breeding populations. Location Europe, Africa. Methods Migration data were recorded using different devices (geolocators, satellite transmitters, Global Positioning System dataloggers) from 87 individuals breeding in the three core European populations, located in the Iberian, Italian and Balkan peninsulas. We estimated connectivity by the Mantel correlation coefficient ( r M ), and computed both the degree of separation between the non‐breeding areas of individuals from the same population (i.e. the population spread) and the relative size of the non‐breeding range (i.e. the non‐breeding range spread). Results European lesser kestrels migrated on a broad front across the Mediterranean Sea and Sahara Desert, with different populations using different routes. Iberian birds migrated to western Sahel (Senegal, Mauritania, western Mali), Balkan birds migrated chiefly to central‐eastern Sahel (Niger, Nigeria, Chad), whereas Italian ones spread from eastern Mali to Nigeria. Spatial differentiation of non‐breeding areas led to a strong migratory connectivity ( r M = .58), associated with a relatively high population (637 km) and non‐breeding range (1,149 km) spread. Main conclusions Our comprehensive analysis of the non‐breeding distribution of European lesser kestrel populations revealed a strong migratory connectivity, a rare occurrence in long‐distance avian migrants. The geographical conformation of the species’ breeding and non‐breeding ranges, together with broad‐front migration across ecological barriers, promoted the differentiation of migratory routes and non‐breeding areas. Strong connectivity could then arise because of both high population spread and broad non‐breeding range.

Reassessment of the size of the Scopoli’s Shearwater population at its main breeding site resulted in a tenfold increase: implications for the species conservation - Pierre Defos du Rau; Karen Bourgeois; Mathieu Thévenet; Lise Ruffino; Sylvain Dromzée; Ridha Ouni; Awatef Abiadh; Roger Estève; Jean-Patrick Durand; Lorraine Anselme; Gilles Faggio; Jaber Mohamed Yahya; et al. (Journal of Ornithology, 2015)